Manajemen Penilaian Kinerja Guru Untuk Meningkatkan Kompetensi Guru di SMP Muhammadiyah 48 Medan - A, Aswaruddin; Hadinata, Razak; Franata, Sandy; Gani, Arif Abdul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research is motivated by the low quality and performance of teachers in dealing with work. Teachers experience boredom, tension, and even experience stress which arises from workloads that are too difficult, heavy and excessive, inadequate work time and equipment, resulting in stress for teachers. . The general aim of the research is to describe and analyze teacher performance assessment management in improving teacher competence at SMP Muhammadiyah 48 Medan. This research uses a qualitative approach through descriptive analysis methods with observation, interview and documentation techniques. Management is a typical process aimed at achieving a goal effectively and efficiently. Competency is the knowledge, skills and abilities mastered by someone who have become part of themselves so that they can carry out cognitive, affective and psychomotor behaviors as well as possible. The results of the research show that: 1) Planning shows that the planning aspects have been carried out in accordance with the conditions and capabilities of the school (SMP) concerned, 2) Organizing shows that it is in accordance with the principles of organizing, 3) Implementation has met the criteria for programs in implementing performance teacher, 4) The evaluation is in accordance with established procedures by means at the end of the lesson the facilitator carries out an assessment (supervision), 5) The obstacle is the lack of ability of the principal to carry out supervision effectively and the lack of motivation from the teacher himself, 6) The solution is for the principal to provide Motivation and encouragement for teachers to be enthusiastic in improving their performance.